CORRELATION BETWEEN CLINICAL CHARACTERISTICS OF ANKYLOSING SPONDYLITIS AND WORK CAPACITY AND PRODUCTIVITY - M. V. Podryadnova; R. M. Balabanova; M. M. Urumova; Sh. F. Erdes (Научно-практическая ревматология)
Objective: to study how clinical characteristics of ankylosing spondylitis (AS) affect working efficiency.Subjects and methods. Authors examined 220 patients with AS (162 males and 58 females). Mean age was 35.1±9.5 years, mean age of the disease manifestation – 30.0±9.7 years. Median duration of AS was 73 [5; 396] months. Activity of the disease was high (BASDAI and ASDAS values 4.6±2.1 and 3.3±1.3 respectively). BASFI was increased to 4.1±2.6, HAQ – 0.98±0.64. Work productivity was assessed with WPAI (Work Productivity and ActivityImpairment) questionnaire by four aspects: absenteeism, presenteeism, general reduction in productivity (GRP) and activities of daily living (ADL).Results. Among 220 patients with AS, 133 were employed (60%). Median value of absenteeism comprised 0 [0; 85] %, presenteeism – 40.3±24.4%, GRP – 59.1±32.9%. Mean ADL was 49.8±26.6% less than normal. Inverse correlation was observed between absenteeism and AS duration (R=-0.22). BASDAI correlated with WPAI aspects: absenteeism (R=0.21), presenteeism (R=0.70), GRP (R=0.37) and reduction in ADL (R=0.73). The strongest correlation detected was that between WPAI aspects (R>0.5) and the intensity of pain assessed by visual analogue scale. BASFI index showed moderate correlation – with GRP (R=0.30) and close – with presenteeism and reduction in ADL (R=0.56 and R=0.71 respectively) and did not correlatewith absenteeism.Conclusion. AS activity was the main factor influencing work productivity. Presenteeism correlates with clinical characteristicsof AS considerably stronger than absenteeism. All WPAI aspects correlated with the disease activity and degree of functional impairment.